Negative electrode composition, preparation method thereof, negative electrode slurry, negative electrode and lithium secondary battery

By adding a pH regulator to the negative electrode composition to adjust the pH value, the problem of hydrogen generation in the silicon-based compound electrode composition is solved, the phase stability and safety are improved, and it is suitable for negative electrode materials of lithium secondary batteries.

CN119365993APending Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380049410.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-22
Filing Date
2023-12-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

During the preparation and storage of electrode compositions or slurries containing silicon-based compounds, hydrogen gas is generated due to the surface oxidation reaction, resulting in a low risk of explosion and phase stability.

Method used

By adding pH regulators to the negative polarizer, the hydrogen ion concentration (pH) to more than 5 and less than 7, prevent the oxidation and hydrogen production of the negative active materials.

Benefits of technology

Effectively improve the stability of the negative composition and the negative pulp, reduce the explosion risk caused by hydrogen, and ensure the safety and stability of the lithium secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365993A_ABST
    Figure CN119365993A_ABST
Patent Text Reader

Abstract

The present application relates to a negative electrode composition, a negative electrode paste comprising the same, a negative electrode, a lithium secondary battery, and a method for preparing the negative electrode composition, in which the negative electrode composition comprises a silicon-based active material, a conductive material, a binder, and a pH adjusting agent, and the pH of the negative electrode composition is 5 (inclusive) to 7 (inclusive). The negative electrode composition has the advantage of achieving excellent adhesive strength by adjusting the pH of the whole negative electrode composition, and has the advantage of solving the problems related to the silicon-based active material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0184166 filed on December 26, 2022, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2023-0189478 filed on December 22, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.

[0002] The present application relates to a negative electrode composition, a preparation method thereof, a negative electrode slurry, a negative electrode and a lithium secondary battery. Background Art

[0003] Due to the rapid increase in the use of fossil fuels, there is an increasing demand for the use of alternative or clean energy, and as part of this trend, the most active area of ​​research is the field of power generation and storage using electrochemical reactions.

[0004] Currently, representative examples of electrochemical devices utilizing such electrochemical energy include secondary batteries, which are increasingly being used.

[0005] With the technological development and increase in demand for mobile devices, the demand for secondary batteries as energy sources has increased rapidly. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as such high-capacity lithium secondary battery electrodes, research on the manufacturing method of preparing high-density electrodes with higher energy density per unit volume has been actively carried out.

[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material for inserting and extracting lithium ions from the positive electrode. Silicon-based particles having a high discharge capacity can be used as the negative electrode active material.

[0007] In particular, recently, in response to the demand for high-density energy batteries, silicon-based compounds (such as Si / C or SiO2) having a capacity 10 times or more higher than that of graphite-based materials have been used together. x Research on methods of using silicon-based compounds as negative electrode active materials to increase capacity has been actively conducted. Although silicon-based compounds as high-capacity materials have the advantage of large capacity when compared with graphite used in the prior art, there are problems such as that hydrogen may be generated due to surface oxidation reaction during the preparation and storage of electrode compositions or slurries containing silicon-based compounds, resulting in explosion risks and low phase stability.

[0008] Various approaches have been discussed to address the above issues, but negative electrodes containing silicon-based compounds still face limitations in commercialization due to potential reductions in battery performance and their applications.

[0009] Therefore, in order to improve the above problems, it is necessary to further study a negative electrode composition that includes a silicon-based compound and can reduce the generation of hydrogen from the silicon-based compound. Summary of the invention

[0010] Technical issues

[0011] In order to solve the above problems, the present application is dedicated to providing a negative electrode composition using a pH adjuster to adjust the hydrogen ion concentration (pH), a preparation method thereof, a negative electrode slurry, a negative electrode and a lithium secondary battery.

[0012] Technical Solution

[0013] An exemplary embodiment of the present specification provides a negative electrode composition including: a negative electrode active material including a silicon-based active material; a conductive material; a binder; and a pH adjuster, and the negative electrode composition has a pH of 5 or more and 7 or less when measured at 25°C.

[0014] Another exemplary embodiment provides a negative electrode slurry including the negative electrode composition and a solvent.

[0015] Yet another exemplary embodiment provides a negative electrode including: a negative electrode collector layer; and a negative electrode active material layer obtained by coating the negative electrode slurry on one surface or both surfaces of the negative electrode collector layer.

[0016] Finally, a lithium secondary battery is provided, comprising: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode or the second electrode is the negative electrode.

[0017] Beneficial Effects

[0018] According to the negative electrode composition of an exemplary embodiment of the present invention, by adjusting the hydrogen ion concentration (pH) of the entire negative electrode composition, the following effect is provided: during the preparation or storage of the negative electrode composition and the negative electrode slurry containing the negative electrode composition, hydrogen is prevented from being generated due to surface oxidation reaction. Thus, the phase stability of the negative electrode composition and the negative electrode slurry containing the negative electrode composition can be improved, and the risk of explosion due to the generation of hydrogen can be reduced.

[0019] By using the negative electrode composition according to another exemplary embodiment of the present invention, process safety and stability of a future negative electrode and a lithium secondary battery including the same can be ensured. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1is a photograph showing a state in which a negative electrode composition according to an exemplary embodiment of the present application is stored in a bag for a certain period of time.

[0021] Figure 2 This is a photograph of the negative electrode composition in the prior art after being stored in a bag for a certain period of time. DETAILED DESCRIPTION

[0022] Before describing the present invention, some terms are first defined.

[0023] In the present specification, when a part “comprises” a constituent element, unless otherwise specifically stated, this does not mean that another constituent element is excluded but means that another constituent element may further be included.

[0024] In this specification, "p to q" means a range of "p or more and q or less".

[0025] In the present specification, a polymer contains a monomer as a monomer unit, which means that the monomer participates in a polymerization reaction and is thereby contained in the polymer as a repeating unit. In the present specification, when a polymer contains a monomer, it is interpreted in the same manner as when the polymer contains a monomer as a monomer unit.

[0026] In this specification, "polymer" is understood to be used in a broad sense, including copolymers, unless otherwise specified as a "homopolymer".

[0027] In this specification, the weight average molecular weight (M w ) and number average molecular weight (M n ) is a polystyrene-converted molecular weight measured by gel permeation chromatography (GPC) using commercially available monodisperse polystyrene polymers (standard samples) with various degrees of polymerization for molecular weight determination as standard substances. In this specification, unless otherwise specified, molecular weight refers to weight average molecular weight.

[0028] The present invention will be described in detail below in conjunction with the accompanying drawings so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various forms and is not limited to the following description.

[0029] Negative electrode composition

[0030] An exemplary embodiment of the present specification features a negative electrode composition in which a negative electrode active material includes a silicon-based active material, and a pH is controlled to be 5 or more and 7 or less by including a pH adjuster.

[0031] According to the negative electrode composition of the exemplary embodiment, the pH of the entire negative electrode composition may be adjusted by the pH adjuster, thereby preventing the generation of hydrogen from the negative electrode active material and improving stability when used in the negative electrode in the future.

[0032] Specifically, the negative electrode composition can prevent oxidation of the negative electrode active material (particularly silicon particles) in the negative electrode composition by controlling the overall pH within a range of 5 or more and 7 or less using a pH adjuster.

[0033] In an exemplary embodiment of the present specification, the pH adjuster may include one or more selected from the group consisting of fumaric acid, glutaric acid, oxalic acid, malonic acid, succinic acid, maleic acid, palmitic acid, tartaric acid, formic acid, acetic acid, glycolic acid, sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, sulfonic acid, aminosulfonic acid, lithium hydroxide and sodium hydroxide, but is not limited thereto, as long as it can easily achieve the desired hydrogen ion concentration range.

[0034] In an exemplary embodiment of the present specification, the pH adjuster may be used alone or in combination of two or more different materials.

[0035] In an exemplary embodiment of the present specification, the content of the negative electrode active material may be 60 parts by weight or more based on 100 parts by weight of the negative electrode composition.

[0036] In another exemplary embodiment of the present specification, the content of the negative electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and 95 parts by weight or less, preferably 90 parts by weight or less, based on 100 parts by weight of the negative electrode composition.

[0037] In an exemplary embodiment of the present specification, the negative electrode active material may include one or more selected from silicon-based active materials and carbon-based active materials.

[0038] In an exemplary embodiment of the present specification, the negative electrode active material may consist of a silicon-based active material and a carbon-based active material.

[0039] In the present specification, the capacity of the silicon-based active material is more than 10 times higher than that of the carbon-based active material, and therefore, when the silicon-based active material is applied to the negative electrode, a negative electrode with a higher level of energy density can be achieved even with a thinner thickness than when the carbon-based active material is used alone.

[0040] In another exemplary embodiment of the present specification, when the negative electrode active material consists of a silicon-based active material and a carbon-based active material, a composition ratio of the silicon-based active material to the carbon-based active material may be in the range of 2:98 to 30:70.

[0041] The negative electrode active material according to the exemplary embodiment contains a carbon-based active material as a main component, and thus the following effects can also be provided: Since the volume expansion of the active material during charge and discharge is small, there is little swelling, and the conductive connectivity of the negative electrode is excellent.

[0042] In one exemplary embodiment of the present specification, the silicon-based active material includes one or more selected from SiO x (x = 0) and SiO x (0 < x < 2), and based on 100 parts by weight of the silicon-based active material, 70 parts by weight or more of SiO x (x = 0) may be included.

[0043] In one exemplary embodiment of the present application, for the silicon-based active material, only pure silicon (Si) may be used as the silicon-based active material. Using pure silicon (Si) as the silicon-based active material may mean that, based on a total of 100 parts by weight of the above silicon-based active material, pure Si particles (SiO x (x = 0)) not combined with other particles or elements are included in the above range.

[0044] In another exemplary embodiment, based on 100 parts by weight of the silicon-based active material, the silicon-based active material may include 70 parts by weight or more, preferably 80 parts by weight or more, more preferably 90 parts by weight or more, or 100 parts by weight or less, preferably 99 parts by weight or less, more preferably 95 parts by weight or less of SiO x (x = 0).

[0045] In the present specification, although the content of the silicon-based active material is large, the significance of the negative electrode composition containing the silicon-based active material within the above content range is that by using a pH regulator to adjust the pH of the negative electrode composition, the amount of hydrogen gas generated by the silicon-based active material is very small.

[0046] In another exemplary embodiment of the present specification, the conductive material and the binder included in the negative electrode composition are both used for the negative electrode composition, and may be respectively referred to as a negative electrode conductive material; and a negative electrode binder.

[0047] The negative electrode composition according to the exemplary embodiment has the following characteristics: By using the silicon-based active material within the above range and using a specific conductive material and a specific binder that can suppress the volume expansion rate during charge and discharge, even if the silicon-based active material is used in the above range, the performance of the negative electrode does not deteriorate, and the output characteristics during charge and discharge are excellent.

[0048] In one exemplary embodiment of the present specification, the silicon-based active material may include one or more selected from SiOx (x = 0), SiO x (0 < x < 2), SiC, and one or more of Si alloys.

[0049] In this specification, the silicon-based active material may exist, for example, in a crystalline or amorphous form. Specifically, the silicon particles of the silicon-based active material may preferably be spherical particles, but are not limited thereto.

[0050] In this specification, the case of SiO2 when x is 2 in SiO is not included because this SiO2 does not react with lithium ions and thus cannot store lithium. Therefore, it is preferred that x is within the range of the exemplary embodiment. x When x is 2 in SiO2, this SiO2 does not react with lithium ions and thus cannot store lithium. Therefore, it is preferred that x is within the range of the exemplary embodiment.

[0051] In this specification, the silicon-based active material may be Si / C composed of a composite of Si and C, or Si.

[0052] In this specification, two or more of the silicon-based active materials may be used in combination.

[0053] In one exemplary embodiment of this specification, the carbon-based active material may include one or more selected from artificial graphite, natural graphite, hard carbon, and soft carbon.

[0054] In one exemplary embodiment of this specification, based on 100 parts by weight of the negative electrode composition, the content of the conductive material may be 0.03 parts by weight or more and 40 parts by weight or less.

[0055] In another exemplary embodiment of this specification, based on 100 parts by weight of the negative electrode composition, the content of the conductive material may be 0.03 parts by weight or more and 40 parts by weight or less, preferably 0.05 parts by weight or more and 30 parts by weight or less, and more preferably 0.5 parts by weight or more and 25 parts by weight or less.

[0056] In one exemplary embodiment of this specification, the conductive material may include one or more selected from dot-shaped conductive materials, planar conductive materials, and linear conductive materials.

[0057] In one exemplary embodiment of this specification, the conductive material may include a dot-shaped conductive material and a linear conductive material.

[0058] In this specification, the point-shaped conductive material can be used to improve the conductivity of the negative electrode, and refers to a point-shaped or spherical conductive material that has conductivity without causing chemical changes. Specifically, the point-shaped conductive material can be at least one selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and from the perspective of achieving high conductivity and excellent dispersibility, it can preferably contain carbon black and / or artificial graphite.

[0059] In the present specification, the planar conductive material can increase the surface contact between the silicon particles in the negative electrode to improve the conductivity, while inhibiting the disconnection of the conductive path caused by volume expansion. The planar conductive material can be a plate-like conductive material or a block-like conductive material. Examples of the planar conductive material may include at least one selected from plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.

[0060] In the present specification, the linear conductive material may be a carbon nanotube. The carbon nanotube may be a bundle type carbon nanotube. The bundle type carbon nanotube may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" used herein refers to a secondary shape in which a plurality of carbon nanotube units are arranged side by side in an orientation (in which the longitudinal axes of the carbon nanotube units are substantially the same) or are intertwined with each other in a bundle or rope shape. In the carbon nanotube unit, the graphene sheet has a cylindrical shape with a nanometer-scale diameter and has a sp 2 In this case, the carbon nanotube unit can exhibit the characteristics of a conductor or a semiconductor according to the structure of the graphite sheet and the winding angle. Compared with the entangled type carbon nanotubes, the bundle type carbon nanotubes can be evenly dispersed when preparing the negative electrode, and can improve the conductivity of the negative electrode by smoothly forming a conductive network in the negative electrode.

[0061] In another exemplary embodiment of the present specification, the conductive material may be a negative electrode conductive material.

[0062] In this specification, the negative electrode conductive material is applied to the negative electrode, and has a completely different structure from the positive electrode conductive material applied to the positive electrode. In other words, the negative electrode conductive material is used to serve as a contact point between the silicon-based active material (where the negative electrode has a very large volume expansion due to charge and discharge), while the positive electrode conductive material plays a role in imparting partial conductivity and at the same time plays a role as a buffer during rolling, so the structure and role of the negative electrode conductive material and the positive electrode conductive material are different.

[0063] In an exemplary embodiment of the present specification, the content of the binder may be 2 parts by weight or more and 30 parts by weight or less, based on 100 parts by weight of the negative electrode composition.

[0064] In another exemplary embodiment of the present specification, the content of the binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, or may be 2 parts by weight or more, 5 parts by weight or more, and 10 parts by weight or more, based on 100 parts by weight of the negative electrode composition.

[0065] In another exemplary embodiment of the present specification, the binder may be a negative electrode binder.

[0066] In an exemplary embodiment of the present specification, the binder may have a weight average molecular weight of 100,000 g / mol or more and 1,500,000 g / mol or less.

[0067] According to the exemplary embodiment, it is characterized in that the mechanical strength is excellent because the weight average molecular weight of the binder satisfies the above range, and the adhesive strength of the binder is excellent because the interaction between molecules is high. In addition, when the above range is satisfied, the viscosity of the binder can be selected within an appropriate range, so that when the negative electrode is manufactured using the binder, the coating property is excellent.

[0068] In an exemplary embodiment of the present specification, the binder is a water-based binder, and the water-based binder may include one or more selected from the following: carboxymethyl cellulose-based binders and their derivatives, polyacrylic acid (PAA)-based binders, polyvinyl alcohol (PVA)-based binders, polyacrylonitrile (PAN)-based binders, and polyacrylamide (PAM)-based binders, which are included as polymer resins having at least one carboxyl group.

[0069] In another exemplary embodiment of the present specification, the water-based binder may be a polymer including one or more monomers selected from the group consisting of (meth)acrylamide, (meth)acrylic acid, and (meth)acrylonitrile.

[0070] In the present specification, a polymerization initiator is used to prepare the adhesive, and ammonium persulfate may be used as an example of the polymerization initiator, but the polymerization initiator is not limited thereto.

[0071] In the present specification, that the adhesive contains a plurality of compounds having a specific ratio (expressed in parts by weight or weight ratio) may mean that each compound (eg, acrylamide, acrylic acid, and acrylonitrile) is contained as a monomer of the adhesive polymer.

[0072] In the present specification, the binder contains a plurality of compounds as monomers, and a monomer contained in the largest content is regarded as a representative monomer, and thus may be named as a "monomer" system compound.

[0073] In the present specification, the term "(meth)acrylic acid" may refer to methacrylic acid and / or acrylic acid.

[0074] In the present specification, when two or more of the binder materials are used to prepare a copolymer having two or more monomers, the ratio of each monomer is not particularly limited as long as it belongs to a water-based binder.

[0075] <Negative electrode slurry>

[0076] An exemplary embodiment of the present invention provides a negative electrode slurry including the negative electrode composition and a solvent.

[0077] In another exemplary embodiment of the present invention, the solvent may include a solvent known in the art, for example, the solvent may be water (eg, distilled water) or NMP, but is not limited thereto.

[0078] In some cases, the viscosity of the negative electrode slurry can be controlled within an appropriate range by appropriately adjusting the average particle size (D50) of the silicon-based active material or the specific surface area of ​​the particles. When the viscosity of the negative electrode slurry is controlled within an appropriate range, the dispersibility of the components in the slurry (e.g., conductive material, binder, silicon-based active material, carbon-based active material, etc.) can be improved. Therefore, the contact area between the components increases, so that the conductive network can be maintained, the capacity retention rate can be improved, and the current density non-uniformity during the charge / discharge process can be prevented.

[0079] In some cases, the viscosity of the negative electrode slurry may be adjusted to 5000 cps to 6000 cps. When the above viscosity range is satisfied, storage properties are excellent, and when the negative electrode slurry is coated on one or both surfaces of an electrode collector layer in the future, coating properties are excellent.

[0080] <Negative electrode>

[0081] An exemplary embodiment of the present specification provides a negative electrode including: a negative electrode collector layer; and a negative electrode active material layer obtained by coating the negative electrode slurry on one surface or both surfaces of the negative electrode collector layer.

[0082] In this specification, the thickness of the negative electrode collector layer is generally 1 μm to 100 μm. The negative electrode collector layer is not particularly limited as long as it has high conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel, etc., are used. The surface is treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. In addition, the negative electrode collector layer can also improve the bonding strength of the negative electrode active material by forming fine concave-convex on its surface. The negative electrode collector layer can be used in various forms such as film, sheet, foil, net, porous body, foam, non-woven fabric, etc.

[0083] Another exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, wherein the thickness of the negative electrode collector layer is 1 μm or more and 100 μm or less, and the thickness of the negative electrode active material layer is 20 μm or more and 500 μm or less.

[0084] However, the thickness may be variously changed according to the type and purpose of the negative electrode used, and is not limited thereto.

[0085] <Lithium Secondary Battery>

[0086] An exemplary embodiment of the present invention provides a lithium secondary battery including: a first electrode; a second electrode; a separator disposed between the first electrode and the second electrode; and an electrolyte, wherein either the first electrode or the second electrode is the above-mentioned negative electrode.

[0087] Specifically, the first electrode may be the negative electrode, and the second electrode may be the positive electrode; or the first electrode may be the positive electrode, and the second electrode may be the negative electrode.

[0088] In this specification, a known positive electrode material can be used as the positive electrode unless it departs from the scope of the present invention.

[0089] Specifically, the lithium secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the negative electrode is the same as the negative electrode described above. Since the negative electrode has been described in detail, its detailed description is omitted.

[0090] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including a positive electrode active material.

[0091] In the positive electrode, there is no particular limitation on the positive electrode collector, as long as the positive electrode collector has conductivity without causing chemical changes to the battery, for example, stainless steel, aluminum, nickel, titanium, fired carbon, or a material in which the surface of aluminum or stainless steel is treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode collector can generally have a thickness of 3 μm to 500 μm, and the adhesion of the positive electrode active material can also be enhanced by forming fine concavoconvexities on the surface of the collector. For example, the positive electrode collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.

[0092] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material includes: a layered compound such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or a compound replaced by one or more transition metals; a lithium iron oxide such as LiFe3O4; a lithium manganese oxide such as Li 1+c1 Mn 2-c1 O4 (0≤c1≤0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5 and Cu2V2O7; Ni-site lithium nickel oxide, represented by the chemical formula LiNi 1-c2 M c2 O2 (herein, M is at least one selected from Co, Mn, Al, Cu, Fe, Mg, B and Ga, and c2 satisfies 0.01≤c2≤0.3); lithium manganese composite oxide, represented by the chemical formula LiMn 2-c3 M c3 O2 (here, M is at least one selected from Co, Ni, Fe, Cr, Zn and Ta, and c3 satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (here, M is at least one selected from Fe, Co, Ni, Cu and Zn); LiMn2O4 in which the chemical formula Li is partially replaced by alkaline earth metal ions, etc., but not limited thereto. The positive electrode may be Li metal.

[0093] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.

[0094] In this case, the positive electrode conductive material is used to impart conductivity to the positive electrode, and can be used without particular limitation as long as the positive electrode conductive material has electronic conductivity without causing chemical changes to the constituted battery. Specific examples thereof include: graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and any one thereof or a mixture of two or more thereof may be used.

[0095] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples thereof may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.

[0096] The diaphragm separates the negative electrode and the positive electrode, and provides a channel for the movement of lithium ions, and can be used without particular restriction, as long as the diaphragm is generally used as a diaphragm in a secondary battery, in particular, it is preferred to have excellent electrolyte moisture retention and a diaphragm with low resistance to the movement of ions in the electrolyte. Specifically, a porous polymer film can be used, for example, a porous polymer film formed by a polyolefin-based polymer (such as, ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers thereof. In addition, a typical porous non-woven fabric can also be used, for example, a non-woven fabric made of glass fiber, polyethylene terephthalate fiber, etc. with a high melting point. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or multilayer structure.

[0097] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, molten inorganic electrolytes, etc., which may be used to prepare lithium secondary batteries, but are not limited thereto.

[0098] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.

[0099] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone (NMP), propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate can be used.

[0100] In particular, among the carbonate-based organic solvents, cyclic carbonates such as ethylene carbonate and propylene carbonate can be preferably used. This is because cyclic carbonates have a high dielectric constant as a high-viscosity organic solvent, thereby dissociating lithium salts well, and when the cyclic carbonates are mixed with linear carbonates (such as dimethyl carbonate and diethyl carbonate) having low viscosity and low dielectric constant in an appropriate proportion, an electrolyte with high conductivity can be prepared, so such a combined use is more preferred.

[0101] As the metal salt, a lithium salt can be used. The lithium salt is a material that is easily dissolved in a non-aqueous electrolyte. For example, as the anion of the lithium salt, a metal salt selected from F - , Cl - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - PF6 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - CF3SO3 - CF3CF2SO3 - 、(CF3SO2)2N - 、(FSO2)2N - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - 、(SF5)3C - 、(CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - 、CH3CO2 - 、SCN- and (CF3CF2SO2)2N - One or more of the following.

[0102] In the electrolyte, in order to improve the service life characteristics of the battery, inhibit the reduction of the battery capacity and improve the discharge capacity of the battery, on the basis of containing the above-mentioned electrolyte components, one or more additives may be included, for example, halogenated alkylene carbonate compounds (such as difluoroethylene carbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, (condensed) glycol dimethyl ethers, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.

[0103] An exemplary embodiment of the present invention provides a battery module including the lithium secondary battery as a unit cell, and a battery pack including the battery module. The battery module and the battery pack include the lithium secondary battery having high capacity, high rate characteristics and cycle characteristics, and can therefore be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0104] Figure 1 is a photograph of a negative electrode composition according to an exemplary embodiment of the present application contained in a battery bag and stored for a certain period of time, Figure 2 This is a photograph of the electrode composition in the prior art after being contained in a battery bag and stored for a certain period of time. Figure 1 and Figure 2 The similarities are that they are all stored at high temperature (about 60°C) for a period of time (about 24 hours), but it can be confirmed that Figure 1 Since the amount of hydrogen produced is small, there is almost no expansion. Figure 2 Due to the large amount of hydrogen produced, the expansion is serious.

[0105] <Method for preparing negative electrode composition>

[0106] An exemplary embodiment of the present invention provides a method for preparing a negative electrode composition, the method comprising: mixing a silicon-based active material, a conductive material, a binder, and a pH adjuster, and the pH of the negative electrode composition can be adjusted to 5 or more and 7 or less using the pH adjuster during the mixing step, or the pH of the negative electrode composition can be adjusted to 5 or more and 7 or less after the mixing step is completed (for example, when a uniform mixture is obtained).

[0107] In this specification, the silicon-based active material, the conductive material, the binder and the pH adjuster are the same as those described above.

[0108] <Method for manufacturing lithium secondary battery>

[0109] An exemplary embodiment of the present invention provides a method for manufacturing a lithium secondary battery, the method comprising:

[0110] preparing a negative electrode slurry by mixing a negative electrode composition with a solvent;

[0111] coating the negative electrode slurry on one surface or both surfaces of an electrode current collector layer; and

[0112] drying the electrode collector layer coated with the negative electrode slurry,

[0113] The negative electrode composition, the solvent, the negative electrode current collector layer and the coating are the same as described above.

[0114] In the present specification, as drying, a method known in the art, such as air drying, etc., is used.

[0115] In the present specification, the step of calendering etc. applied after the above-mentioned steps is known in the art.

[0116] [Implementation Method]

[0117] Preferred embodiments will be presented below to facilitate understanding of the present invention, but these embodiments are only used to illustrate the present invention. It is obvious to those skilled in the art that various modifications and variations can be made within the scope and technical spirit of the present invention, and such modifications and variations also fall within the scope of the appended claims.

[0118] Preparation Example. Preparation of water-based adhesive

[0119] <Preparation Example 1>

[0120] In a reactor equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inflow tube, acrylamide (50% aqueous solution) and acrylic acid (AA, 80% aqueous solution) were used and mixed in a molar ratio of 6:4, and the resulting mixture was reacted at 80° C. for 5 hours to prepare an aqueous polymer (polyacrylamide polymer, aqueous solution state).

[0121] Then, a 0.1 mol (M) NaOH aqueous solution was added dropwise to the aqueous polymer to prepare an aqueous adhesive with a pH of 7.8.

[0122] Example. Preparation of negative electrode slurry

[0123] <Example 1>

[0124] Si with d50 = 5.2 μm was used as the negative electrode active material, three types of conductive materials: carbon black (trade name: Super C65, manufactured by TIMCAL Ltd.), artificial graphite (trade name: SFG6L, manufactured by TIMCAL Ltd.) and SWCNT were used as conductive materials, and the aqueous binder prepared in Preparation Example 1 was used as a binder, and the resulting mixture was mixed so that Si: C65: SFG6L: SWCNT: the binder = 80: 3: 8.5: 0.5: 8 (based on weight ratio), thereby preparing a negative electrode composition. Here, 1 M oxalic acid (pH adjuster) was added thereto so that the final pH of the electrode composition was 5.2.

[0125] Then, water was added as a solvent, and the water content was adjusted in consideration of coating properties, viscosity, and solid content so that the viscosity of the obtained negative electrode slurry was 5000 cps to 6000 cps.

[0126] <Example 2>

[0127] Si with d50 = 5.2 μm was used as the negative electrode active material, three types of conductive materials were used: carbon black (trade name: Super C65, manufactured by Timcole), artificial graphite (trade name: SFG6L, manufactured by Timcole) and SWCNT as conductive materials, the aqueous binder prepared in Preparation Example 1 was used as a binder, and the resulting mixture was mixed so that Si: C65: SFG6L: SWCNT: the binder = 80: 3: 8.5: 0.5: 8 (based on weight ratio), thereby preparing a negative electrode composition. Here, 0.0001 M sulfuric acid (pH adjuster) was added thereto so that the final pH of the electrode composition was 5.5.

[0128] Then, water was added as a solvent, and the water content was adjusted in consideration of coating properties, viscosity, and solid content, so that the viscosity of the obtained negative electrode slurry was adjusted to 5000 cps to 6000 cps.

[0129] <Example 3>

[0130] A negative electrode slurry was prepared in the same manner as in Example 1, except that a mixture of artificial graphite (QCG-N2, produced by Shanshan Technology Co., Ltd.):Si=90:10 was used as the negative electrode active material.

[0131] <Example 4>

[0132] A negative electrode slurry was prepared in the same manner as in Example 1, except that a mixture of artificial graphite (SD5100A, manufactured by Sila Nanotechnologies Inc.):SiC = 90:10 was used as the negative electrode active material.

[0133] <Comparative Example 1>

[0134] Si with d50 = 5.2 μm was used as the negative electrode active material, three types of conductive materials: carbon black (trade name: Super C65, manufactured by Timcole), artificial graphite (trade name: SFG6L, manufactured by Timcole) and SWCNT were used as conductive materials, the aqueous binder prepared in Preparation Example 1 was used as a binder, and the resulting mixture was mixed so that Si:C65:SFG6L:SWCNT:the binder = 80:3:8.5:0.5:8 (based on weight ratio), thereby preparing a negative electrode composition.

[0135] Then, water was added as a solvent, and the water content was adjusted in consideration of coating properties, viscosity, and solid content so that the viscosity of the obtained negative electrode slurry fell within the range of 5000 cps to 6000 cps (assuming that the pH of the electrode composition state was 7.4).

[0136] <Comparative Example 2>

[0137] The preparation method of the negative electrode slurry is the same as that of Comparative Example 1, except that a mixture of artificial graphite (QCG-N2, manufactured by Shanshan Technology): Si=90:10 is used as the negative electrode active material (prerequisite being that the pH of the electrode composition state is 7.6).

[0138] <Comparative Example 3>

[0139] The preparation method of the negative electrode slurry is the same as that of Comparative Example 1, except that a mixture of artificial graphite:SiC = 90:10 is used as the negative electrode active material (provided that the pH of the electrode composition state is 7.5).

[0140] <Comparative Example 4>

[0141] The preparation method of the negative electrode slurry was the same as that of Comparative Example 1, except that 0.0001 M nitric acid was additionally added in Comparative Example 1 so that the final pH of the electrode composition was 4.2.

[0142] <Comparative Example 5>

[0143] The preparation method of the negative electrode slurry is the same as that of Comparative Example 1, except that 100% natural graphite is used in Comparative Example 1.

[0144] Experimental example

[0145] <Experimental Example 1: Evaluation of Hydrogen Generation Amount>

[0146] The negative electrode slurries of Examples 1 to 4 and Comparative Examples 1 to 5 were stored at 60° C. overnight, and the amount of generated hydrogen was measured.

[0147] Specifically, the amount of hydrogen generated can be specifically obtained by each putting 5 g of the negative electrode slurry into a 9 cm×9 cm bag, sealing the bag, and then placing the bag in a constant temperature chamber at 60° C. for 24 hours, collecting the gas generated in the bag and performing quantitative analysis by GC / MS.

[0148] <Experimental Example 2: Battery Manufacturing and Evaluation of Battery Characteristics>

[0149] The negative electrode slurries of Examples 1 to 4 and Comparative Examples 1 to 5 were respectively coated on copper foils with a thickness of 18 μm and dried, and an active material layer with a thickness of 50 μm was formed on one surface of the copper foil. The copper foil was punched into a circle with a diameter of 14 Φ (mm) to manufacture a test electrode (negative electrode). A metal lithium foil with a thickness of 0.3 mm was used as the positive electrode, and a porous polyethylene sheet with a thickness of 0.1 mm was used as the separator. In addition, LiPF6 was dissolved as a lithium salt in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1 at a concentration of about 1 mol / L to obtain an electrolyte as an electrolyte.

[0150] The negative electrode, the positive electrode, the separator and the electrolyte were sealed in a stainless steel container to prepare a coin cell for evaluation with a thickness of 2 mm and a diameter of 32 mm. The coin cell was charged at a constant current of 0.05C until the voltage reached 0.01V, and discharged at a constant current of 0.05C until the voltage reached 1.0V to determine the initial (discharge) capacity. After that, for the cycle characteristics, a capacity retention rate test was performed at a constant current of 0.2C within the same voltage range as above, and the results are shown in Table 1 below.

[0151]

[0152] As shown in Table 1 above, it can be seen that in the batteries using the negative electrode slurry whose pH of the electrode composition satisfies the range of 5 to 7 by using the pH adjuster (Examples 1 to 4), the amount of hydrogen generated is small compared with Comparative Examples 1 to 4, and the cycle capacity retention rate is excellent.

[0153] Specifically, in the case of Comparative Example 4 in which the pH of the electrode composition was less than 5, the amount of hydrogen generated was low, but even if Si was used as the negative electrode active material, the capacity retention rate was very low. In addition, it can be seen that Comparative Examples 1 to 3 in which the pH of the binder exceeded 7 were not suitable for use as negative electrode compositions because the amount of hydrogen generated was 28,000 μL or more even though the capacity retention rate was as high as 80% or more.

[0154] In addition, in Comparative Example 5, the negative electrode active material is composed of graphite. Although the capacity retention rate and hydrogen generation amount are good, the initial capacity is less than 400 mAh / g, so it is not suitable for manufacturing a high-capacity battery and is therefore determined to be unsuitable.

Claims

1. A negative electrode composition, comprising: A negative electrode active material, wherein the negative electrode active material comprises a silicon-based active material; Conductive materials; Adhesives; and pH adjusters, in, The pH is 5 or more and 7 or less when measured at 25°C.

2. The negative electrode composition according to claim 1, wherein The pH adjuster comprises at least one selected from the group consisting of fumaric acid, glutaric acid, oxalic acid, malonic acid, succinic acid, maleic acid, palmitic acid, tartaric acid, formic acid, acetic acid, glycolic acid, sulfuric acid, hydrochloric acid, phosphoric acid, nitric acid, sulfonic acid, aminosulfonic acid, lithium hydroxide and sodium hydroxide.

3. The negative electrode composition according to claim 1, wherein The negative electrode active material may be contained in an amount of 60 parts by weight or more based on 100 parts by weight of the negative electrode composition. 4 . The negative electrode composition according to claim 1 , wherein the negative electrode active material further comprises a carbon-based active material.

5. The negative electrode composition according to claim 1, wherein The silicon-based active material includes one or more selected from SiO where x = 0 x , SiO where 0 < x < 2 x , SiC, and Si alloys.

6. The negative electrode composition according to claim 1, wherein The silicon-based active material includes one or more selected from SiO where x = 0 x and SiO where 0 < x < 2 x Among them, based on 100 parts by weight of the silicon-based active material, the silicon-based active material includes 70 parts by weight or more of SiO where x = 0 x .

7. The negative electrode composition according to claim 4, wherein The carbon-based active material includes one or more selected from artificial graphite, natural graphite, hard carbon and soft carbon.

8. The negative electrode composition according to claim 1, wherein The conductive material includes at least one selected from point-shaped conductive materials, surface-shaped conductive materials, and line-shaped conductive materials.

9. The negative electrode composition according to claim 1, wherein the binder is an aqueous binder, and The water-based adhesive comprises one or more selected from the following: Carboxymethyl cellulose-based binders and derivatives thereof included as polymer resins having at least one carboxyl group; Polyacrylic acid (PAA) based adhesive; Polyvinyl alcohol (PVA) based adhesive; Polyacrylonitrile (PAN) based adhesive; and Polyacrylamide (PAM) based adhesive. 10 . A negative electrode slurry, comprising the negative electrode composition according to claim 1 and a solvent.

11. A negative electrode, comprising: a negative electrode current collector layer; and A negative electrode active material layer is obtained by coating the negative electrode slurry according to claim 10 on one surface or both surfaces of the negative electrode collector layer.

12. A lithium secondary battery, comprising: a first electrode; a second electrode; A separator disposed between the first electrode and the second electrode; and Electrolytes, in, Either the first electrode or the second electrode is the negative electrode according to claim 11.